Assessment of public health notification thresholds for Clostridioides difficile in acute-care hospitals—Colorado and Tennessee, 2018. (4th November 2021) - Parikh, Meghana P.; Dale, Ariella P.; Bamberg, Wendy M.; Kainer, Marion A.
Abstract: Objectives: We aimed to identify a threshold number of Clostridioides difficile infections (CDI) for acute-care hospitals (ACHs) to notify public health agencies of outbreaks and we aimed to determine whether thresholds can be used with existing surveillance strategies to further infection reduction goals. Design: Descriptive analysis of laboratory-identified CDI reported to the National Healthcare Safety Network by Colorado and Tennessee ACH inpatient units in 2018. Methods: Threshold levels of ≥2, ≥3, and ≥4 CDI events per calendar month per unit (unit month) were assessed to identify units that would trigger facility reporting to public health. Values meeting thresholds were defined as alerts. Recurrent alerts were defined as alerts from units meeting the threshold ≥2 times within 12 months. The presence of alerts was compared to the number of excess infections to identify high-burden facilities. Results: At an alert threshold of ≥2 CDI events per unit month, 204 alerts occurred among 43 Colorado ACHs and 290 among 78 Tennessee ACHs. At a threshold of ≥3, there were 59 and 61 alerts, and at a threshold of ≥4, there were 17 and 10 alerts in Colorado and Tennessee, respectively. In both Colorado and Tennessee, at a threshold of ≥3 nearly 50% of alerts were recurrent, and facilities with at least one alert in 2018 accounted for ∼85% of the statewide excess infections. Conclusions: An alert threshold of ≥3 CDI events per unit month is feasible for rapid identification of outbreaks in ACHs. This threshold can facilitate earlier assessments and interventions in high-burden facilities.